Arte e História : as esculturas dos guerrilheiros da Gruta de São Quirino em Irupi-ES como dispositivo de análises para a Guerrilha do Caparaó - Lucio, Gabriela Ferreira (2020)
The Caparaó Guerrilla was a resistance movement against the Military Dictatorship in Brazil, which occurred in the division between the states of Espírito Santo and Minas Gerais, in 1966 and 1967. The particularity of movement consists in the majority composition of this group of military personnel, as a result of a 1964 coup. This research has an exploratory character, which investigates from sculptures of guerrillas of the Gruta de São Quirino, located in the municipality of Irupi- ES, a relationship that is between a work and a community. In this sense, how sculptures are understood as a device that allows the interaction between Art and History. In addition, the objective is the analysis of this work, its installation in the space of nature (forest), seeking to reproduce, based on oral testimonies, as articulations and strategies that involve the context of the guerrillas for the members of the region